2018
DOI: 10.13181/mji.v27i4.2107
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic versus land-based exercise for cardiorespiratory endurance and quality of life in obese patients with knee osteoarthritis: a randomized controlled trial

Abstract: Background: Obesity with knee osteoarthritis (OA) is related to chronic pain causing physical inactivity that leads to decreased cardiorespiratory endurance and quality of life. Aquatic and land-based exercises are effective in improving physical activity. The aim of this study is to compare between aquatic and land-based exercise to improve cardiorespiratory endurance and quality of life in obese patients with knee osteoarthritis.Methods: A single-blind, randomized, controlled trial was conducted on thirty th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…Eight original studies included subjects with comorbidities: metabolic syndrome 35 or diabetes. 36 , 37 , 38 , 39 , 40 , 41 , 42 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight original studies included subjects with comorbidities: metabolic syndrome 35 or diabetes. 36 , 37 , 38 , 39 , 40 , 41 , 42 …”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies involved an aerobic‐only exercise program, eight studies comprised a resistance‐only exercise program, and six studies involved a combined aerobic plus resistance exercise program. A few studies included water exercise, 42 , 43 , 44 , 45 pilates, 46 and multicomponent programs also involving balance or flexibility exercises. 47 , 48 Twenty‐four studies involved a passive control, two studies combined exercise with diet and involved a diet‐only control, and two studies were comparative, involving two different exercise groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Any type of exercise that leads to calorie-burning increases the likelihood of alterations in body composition. Water aerobics does this with internal resistance to water viscosity and creates pressure in any movement (Tamin & Loekito, 2018). Thus, the moderate weight loss experienced during the WA-TERinMOTION aquatic exercise was most likely induced by a lack of compensatory increase in calorie intake to match energy expenditure during training.…”
Section: Discussionmentioning
confidence: 99%
“…Raffaelli et al (2010) found that aquatic exercise compared to land-based exercise led to noticeable rises in physical activity. Aquatic exercise is defined as a low-impact activity that occurs in water (Sanders et al, 2016), which, due to greater resistance than air, increases heart rate and energy flow and includes movements of the whole body (Tamin & Loekito, 2018).…”
Section: Introductionmentioning
confidence: 99%